(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Judicial appeal against decisions adopted by state tax authorities and actions (or inaction) of their officials constitutes an essential guarantee for the protection of taxpayers’ rights. Although the legislation of the Republic of Uzbekistan establishes procedures and time limits in this sphere, practical implementation reveals certain problems and legal gaps. In particular, issues concerning appeal deadlines, the complexity of judicial proceedings, the scope of judicial review over tax authority decisions, and the personal liability of officials who adopt unlawful decisions remain relevant. In the context of digitalization, tax administration mechanisms are being modernized; however, reliance on automated systems and data processing may lead to erroneous or unlawful decisions adversely affecting entrepreneurs, including damage to their business reputation. This article examines civil law mechanisms for compensating both material damage and reputational harm caused by unlawful tax decisions, based on comparative analysis of the legal systems of Germany, France, and the United States. The study identifies deficiencies in Uzbek legislation and proposes reforms aimed at strengthening compensation mechanisms, particularly in relation to business reputation and non-material damage.